Genetic Transformation Of Oncidium Sharry Baby Using Biolistic Method - Ng, Chea Yee (2007)

(untitled)
Orchid is one of the most important export commodities in Malaysia. To remain globally competitive the orchid industry needs to constantly improve the quality and variety of flowers exported. Genetic modification of orchids to create varieties will help to boost the orchid industry in Malaysia. The aim of this study was to develop an optimized transformation procedure using the PDS-He 1000 biolistic system for the introduction of potential genes of interest into Oncidium Sharry Baby protocorm-like-bodies (PLB). Determination of the minimal inhibitory concentration of hygromycin to select transformed PLB showed that 100% non-transformed PLB were killed at 5.0 μg/ml hygromycin. Optimization of the transformation parameters (time course of GFP transient expression in PLB, concentration of DNA, age of PLB, presence of spermidine and CaCl2 in DNA-microcarrier precipitation and duration of single PLB in fresh medium prior bombardment) were achieved by co-bombarding the PLB with the plasmids p35S, which carries a synthetic green fluorescence protein (sgfp) gene, and pSM-CHS, which carries the antisense chalcone synthase (CHS) and a hygromycin resistance (hptII) genes. Optimized parameters were chosen based on GFP expression in transformed PLB and the number of survivals on hygromycin selection. The results showed that the highest GFP expression was observed in 4 weeks old PLB on the second day post-bombardment using 1.0μg DNA per bombardment. Pre-incubation of the PLB for 3 days on fresh medium prior to bombardment also enhanced GFP expression. Using spermidine alone in DNA-microcarriers precipitation process was shown to result in high GFP expression. PLB obtained from each of the parameters optimization step were subjected to 5.0 μg/ml hygromycin selection and the percentage of surviving plantlets was recorded. The highest number of survivals was obtained when 0.5 μg DNA per bombardment were used on 2 weeks old PLB which had undergone 1 day pre-treatment on fresh medium prior to the bombardment. The DNA was prepared with the presence of CaCl2 in the DNA-microcarriers precipitation process. After 8 months of hygromycin selection, three types of plantlets, designated as Type A, Type B and Type C, were identified based on their growth morphology on the regeneration medium. Type A plantlet never attained more than one centimeter in height before tissue necrosis set in. Type B plantlet was dwarf-like when compared to normal plant. Type C showed normal growth comparable to untransformed plantlet. Randomly picked leaves were viewed under Environmental Scanning Electron Microscopy (ESEM), which revealed a reduction in stomata number for Type A plantlet and altered shape of the guard cells. Type B showed a combination of both normal and abnormal stomata. Type C plantlet possessed normal stomata with typical guard cell shape. Subsequently, the presence of the transgenes (sgfp, hptII and antisense CHS) in the genome of putative transformants were verified by polymerase chain reaction (PCR). Genomic DNA were obtained from randomly selected transformants and subjected to PCR analyses. About 81.3 % of Type A, 1.4 % of Type B, and 3.2 % of Type C transformants successfully showed amplification of the expected band size of CHS antisense gene. While 81.3 % of Type A, 76.1 % of Type B, and 83.9 % of Type C successfully amplified the expected band size of hptII gene. About 56.3 % of Type A, 26.8 % of Type B, and 35.5 % of Type C amplified the expected band size of sgfp gene. An optimized transformation system has been established using biolistic method for Oncidium Sharry Baby PLB with 12.7%, 24.5% and 78.8 % transformation frequencies for antisense CHS, sgfp and hptII genes, respectively. Hygromycin at 5.0 μg/ml is a good selective agent for Oncidium Sharry Baby transformation.